You have to find first the discriminant
∆=8^2-4*(-1) *(-7) =36
x=(-8±√36) /-2=(-8±6)/-2=4±3=1 or 7
So x(1)=1 or x(2)=7
-x^2+8x-7=[x-x(1) ][x-x(2) ]=(x-1) (x-7)
By substitution is how to solve
2x-3y=21
y=3-x
2x-3(3-x)=21
2x-9+3x=21
5x=30
x= 6
now substitute our x value into y=3-x
so we get
y=3-6 = -3
so x=6 and y=-3 hope this helps!!!!! Thank you!
Answer:
238
Step-by-step explanation:
The answer i got is VP<------------->
AKA the first option
i hope this is right
Answer:
I think the answer is 40. it will take about 20 months to have 100 dollars